2013
DOI: 10.3109/10715762.2013.845664
|View full text |Cite
|
Sign up to set email alerts
|

Onion extract structural changes duringin vitrodigestion and its potential antioxidant effect on brain lipids obtained from low- and high-fat-fed mice

Abstract: This study investigated the effects of onion (Allium cepa, L.) extract on the antioxidant activity of lipids in low-and high-fat-fed mouse brain lipids and its structural change during in vitro human digestion. The onion extracts were passed through an in vitro human digestion model that simulated the composition of the mouth, stomach, and small intestine juice. The brain lipids were collected from low- and high-fat-fed mouse brain and then incubated with the in vitro-digested onion extracts to determine the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
4
10
0
Order By: Relevance
“…The rising of hydrophilic property of GI digests after intestinal phase digestion favors their trapping of the ABTS • + radical (You et al, 2010). This result was agreed with the findings from previous studies which reported the ABTS • + value increased after in vitro digestion (You et al, 2010;Hur et al, 2013;Chen et al, 2014). Phytosterols and tocopherols are the major bioactive compounds in kenaf seed oil, which possess the antioxidant activity (Nyam et al, 2009).…”
Section: Assessment Of Antioxidant Activity After In-vitro Digestionsupporting
confidence: 91%
“…The rising of hydrophilic property of GI digests after intestinal phase digestion favors their trapping of the ABTS • + radical (You et al, 2010). This result was agreed with the findings from previous studies which reported the ABTS • + value increased after in vitro digestion (You et al, 2010;Hur et al, 2013;Chen et al, 2014). Phytosterols and tocopherols are the major bioactive compounds in kenaf seed oil, which possess the antioxidant activity (Nyam et al, 2009).…”
Section: Assessment Of Antioxidant Activity After In-vitro Digestionsupporting
confidence: 91%
“…The protective action mechanisms of the extracts or the phenolic compounds were accompanied by a decrease of the induction of the apoptotic stress markers (p-MAPKAPK-2, p-SAPK/JNK, p-HSP27, p-c-JUN, and cl-CASP3). The findings were related to the cellular protective effects of the extracts, and oleuropein and hydroxytyrosol were comparable with the effects of positive standard [21,22]. The protective action mechanisms of the extracts and the phenolic constituents of olive leaves include the reduction of ROS production and the amelioration of the mitochondria membrane potential in H9c2 cells.…”
mentioning
confidence: 56%
“…This result revealed that the digestibility was shown to have similar between onion quercetin and grape resveratrol during in vitro human digestion (no significantly different). In previous studies, we found that the quercetin concentration in onion extracts was increased by in vitro human digestion, and antioxidant activity was increased by in vitro human digestion of both onion extract and/or quercetin standard [13], [16]. This is because quercetin aglycone was cleaved from rutin glucoside in onion [13].…”
Section: Digestibility Of Onion Quercetin and Grape Resveratrol Durinmentioning
confidence: 93%
“…Indeed, quercetin aglycone has strong antioxidative activity compare to rutin glucoside. Our previous study found that the polyphenols are obviously stable through gastric digestion [16]. Over the left, these polyphenols are great sensitive to the mild alkaline conditions in the small intestine, some compounds may be form of other components and structure via duodenum.…”
Section: Digestibility Of Onion Quercetin and Grape Resveratrol Durinmentioning
confidence: 98%